Single Nucleotide Polymorphisms Identification and Genotyping Analysis of Melanocortin 1 Receptor Gene in Various Plumage Colours Magelang Ducks - Rahayu , Ayu; Purwantini, Dattadewi; Maharani, Dyah; Hartatik, Tety (International Journal of Poultry Science, 2015)
The objective of this study was to investigate the variations in Melanocortin 1 receptor (MC1R) gene and the association with plumage colours in Magelang duck populations using single nucleotide polymorphism (SNP). Forty three genomic DNA samples of Magelang ducks consisted of 3 plumage colour groups of brown, black and white were investigated. Primer design from Anas platyrhynchos complete genome in GenBank Accession Number HQ699486. Primer F:5’-GCTCTTCATGCTGCTGATGG-’3, R:5’-GATGAAGACGGTGCTGGAGA-’3. A 256-bp fragment was amplified by polymorphism chain reaction then sequenced. Two SNPs identified in this study were c.376A>G and c.409G>A. Chi-square (X2) value showed that 0.75 in Magelang ducks had GG genotype; 0.81 for GA genotype; 0.34 for AA genotype (c.376G>A) and 0 for GG genotype; 1.37 for GA genotype; 5.82 for AA genotype (c.409A>G). These results suggested that the MC1R genotype distribution in Magelang duck population with brown, black and white plumage was balanced or not deviated from Hardy Weinberg Equilibrium. Conclusively, two SNPs were identified; c.376A>G SNP that changed the amino acid from isoleucine to valine and valin/isoleucine and c.409G>A SNP that changed alanine to threonine and threonine/alanine.